Krafterra – sacos de cimento (resíduo) na construção civil - Sá Neto, Sebastião Diniz de (Universidade Federal Rural do Semi-Árido, 2018)
Kraft paper is an alternative that came to replace and innovate the conventional materials, focusing on all the environmental apparatus necessary for the regulators on the means of production. It was thought to make feasible a production of kraft paper with a use of raw material: the cement bags. The main objectives of the research are to present a tendency to recycle an alternative source of information and to disseminate a construction forecast related to environmental safety. The research had as objective a research on the kraft paper in which an analysis was made considering several factors like, history, advantages and disadvantages based on articles, dissertations and theses already published. The information was extracted and dissipated in order to prove a usefulness of the paper and a presentation of information that allows a greater understanding of the subject. Due to the facts mentioned in this research, it is possible to conclude that the production and use of kraft paper is quite feasible for civil construction.
Keywords: Material alternativo; Reciclagem; Papel Kraft; Alternative material; Recycling; Kraft paper; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA